2013
DOI: 10.3168/jds.2013-6758
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and hypoallergenic properties of milk protein hydrolysates in ICR mice

Abstract: Approximately 2.5% of young children are allergic to cow milk. In this study, milk protein hydrolysates made from full-cream milk via enzymatic hydrolysis played a positive role in regulating the immune system of ICR mice. Milk protein hydrolysates enhanced immunity in mice by stimulating host immunity, probably by increasing the weight of certain immune system organs, improving the level of hemolysin in serum, and enhancing the phagocytosis of macrophages. Milk protein hydrolysates have the capability to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Often the activity of a whole protein hydrolysate is determined rather than the activities of its component peptides (Liaset et al., ; Pan, Wu, Liu, Cao, & Zeng, ; Sakanaka, Tachibana, Ishihara, & Raj Juneja, ; Shimizu et al., ).Thus, which sequence exhibits a given effect is unknown. Variation of conditions during preparation of hydrolysates, for example, pH, enzymes involved, and temperature, could lead to different peptide mixtures, making it harder to assign specific effects to individual peptides; also, hydrolysates can have a stabilizing effect on particular peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Often the activity of a whole protein hydrolysate is determined rather than the activities of its component peptides (Liaset et al., ; Pan, Wu, Liu, Cao, & Zeng, ; Sakanaka, Tachibana, Ishihara, & Raj Juneja, ; Shimizu et al., ).Thus, which sequence exhibits a given effect is unknown. Variation of conditions during preparation of hydrolysates, for example, pH, enzymes involved, and temperature, could lead to different peptide mixtures, making it harder to assign specific effects to individual peptides; also, hydrolysates can have a stabilizing effect on particular peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Milk is one of the most common food allergens for infants and young children, with an incidence of approximately 2 to 3% in the general population (Bock, 1987;Høst and Halken, 1990;Schrander et al, 1993;Saarinen et al, 2005;Pan et al, 2013). Milk allergies can cause severe adverse reactions, including digestive problems and respiratory disorders such as asthma.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proliferation rates of the MMO-treated groups exceeded that of the negative control group across the board, suggesting a supra-accelerating effect of MMO on CTX-damaged mice. Similarly, Pan et al [35] reported that milk protein hydrolysate (MPH) increased immunological function by triggering hemolysin formation in mice. Liu et al [37] showed that cottonseed meal oligopeptide (PFC) significantly increased the HC 50 levels in mice by 1.39 ± 0.45, 2.59 ± 0.20, and 2.46 ± 0.41 when given doses of 5 mg/mL, 10 mg/mL, and 20 mg/mL, respectively.…”
Section: Serum Hemolysinmentioning
confidence: 98%
“…Hemolysin reflects the proliferation and differentiation of hemolytic B cells and is one of the main nonspecific indexes used to measure the immune function of the body [35,36]. The half hemolysis value (HC 50 ) and the hemolysin proliferation rate are routinely used to evaluate the effects of natural extract products on humoral immunity in mice [36].…”
Section: Serum Hemolysinmentioning
confidence: 99%